Why Copious Resources of Africa and Massive Dependence on Foreign Aid: Leadership Protagonists Towards Sustainable Development - Aderogba, Kofo; Adeniyi, Kunle; Komolafe, Bolaji; Bankole, Mike; Isele, Tolu (Mahesa Research Center, 2025)
The states of Africa face many developmental challenges despite their huge resource endowments. The work gives a swift overview of the resources and the associated developmental challenges; queries dependence on foreign Aid; and makes recommendations for sustainable development. It is nonempirical - It relies on theories, methods, personal observations, and contemporary events. The continent is home to many resource-dense natural habitats. The natural resource economy contributes significantly to the built environment, but the continent faces challenges in protecting and using its resources. The resources are also vulnerable to environmental risks, and there is exploitation of the local workers and other human rights concerns. States still depend on foreign Aid. African States should be reluctant to accept foreign aid assistance. However, if there are any needs, there must be reform. There should be massive technological transfer and an emphasis on STEM education to sustainably explore, exploit, develop, and market the resources. With visionary leadership, profitably growing resources, and reforming Aid, foreign Aid will stimulate growth and development and achieve the 2063 agenda. Further research is required into the dependence on foreign Aid in Africa.